Diagnostic delay in narcolepsy type 1: combining the patients' and the doctors' perspectives. (6th May 2016) - Taddei, Raquel N.; Werth, Esther; Poryazova, Rositsa; Baumann, Christian R.; Valko, Philipp O.
Summary: Narcolepsy type 1 is a neurological disorder characterized by a unique syndrome, including the pathognomonic symptom of cataplexy. The diagnosis can be confirmed by objective measures, such as typical findings in the multiple sleep latency test, reduced or undetectable levels of orexin (hypocretin) in the cerebrospinal fluid, and linkage to a specific HLA haplotype. Nevertheless, the mean time that elapses from symptom onset to the correct diagnosis ranges between 10 and 20 years, and the causes and correlates of this delay are poorly understood. Diagnostic delay was assessed on 52 well‐defined patients with narcolepsy type 1, evaluating clinical, electrophysiological and neurochemical parameters and the results of a 41‐item questionnaire developed to obtain the patients' perspective on various aspects of the diagnostic process. The mean time gap between disease onset and first medical consultation was 3.2 ± 5.1 years; the mean diagnostic delay was 8.9 ± 11.0 years. Prior to correct diagnosis, patients received a wide variety of misdiagnoses. The self‐ratings of the patients revealed that the undiagnosed symptoms caused high levels of anxiety and unjustified criticism by family, friends and employers. Multiple regression analysis identified higher cerebrospinal fluid orexin levels ( β  = 0.311, P  = 0.01), and a longer interval between the onset of excessive daytime sleepiness and cataplexy ( β  = 0.368, P  = 0.002) as independent associates of longer diagnostic delay. The diagnostic delay decreased over the last decades ( β  = −0.672, P  < 0.001). In conclusion, delayed diagnosis of narcolepsy type 1 is very common, associated with many adverse consequences, and requires educational efforts to improve awareness on narcolepsy among healthcare providers and the general population.